2016
DOI: 10.1158/1535-7163.mct-15-0688
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Eribulin and Aurora A Inhibitor MLN8237 Prevents Metastatic Colonization and Induces Cytotoxic Autophagy in Breast Cancer

Abstract: Recent findings suggest that the inhibition of Aurora A (AURKA) kinase may offer a novel treatment strategy against metastatic cancers. In the current study, we determined the effects of AURKA inhibition by the small molecule inhibitor MLN8237 both as a monotherapy and in combination with the microtubule targeting drug eribulin on different stages of metastasis in triple negative breast cancer (TNBC) and defined the potential mechanism of its action. MLN8237 as a single agent and in combination with eribulin a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…1×10 6 MDA-MB-231-luc2 cells expressing doxycycline-inducible pTRIPZ-RFP-shControl or shNEDD9 (25) were suspended in 4mg/ml Matrigel (Trevigen) and injected into the mammary fat pad of 6–8-weeks old immunodeficient female NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice (Jackson Laboratory). Mice with mammary tumors (150–200mm 3 ) were pre-treated in neoadjuvant settings with 10mg/kg AURKA inhibitor MLN8237 via oral gavage for 1 week (4 days on, 3 days off) as previously described to temporarily halt metastasis, but continue mammary tumor growth (31). shRNA expression in tumor cells was induced via introduction of doxycycline-containing food (Bio-Serv) in combination with vehicle or 10mg/kg Y-27632 which was administered by oral gavage for 3 weeks (4 days on, 3 days off).…”
Section: Methodsmentioning
confidence: 99%
“…1×10 6 MDA-MB-231-luc2 cells expressing doxycycline-inducible pTRIPZ-RFP-shControl or shNEDD9 (25) were suspended in 4mg/ml Matrigel (Trevigen) and injected into the mammary fat pad of 6–8-weeks old immunodeficient female NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice (Jackson Laboratory). Mice with mammary tumors (150–200mm 3 ) were pre-treated in neoadjuvant settings with 10mg/kg AURKA inhibitor MLN8237 via oral gavage for 1 week (4 days on, 3 days off) as previously described to temporarily halt metastasis, but continue mammary tumor growth (31). shRNA expression in tumor cells was induced via introduction of doxycycline-containing food (Bio-Serv) in combination with vehicle or 10mg/kg Y-27632 which was administered by oral gavage for 3 weeks (4 days on, 3 days off).…”
Section: Methodsmentioning
confidence: 99%
“…Early results from a Phase I/II alisertib and paclitaxel trial for ovarian and breast cancer reveal partial response in eight patients and stable disease for three patients [ 19 ]. The fact that alisertib, as a single agent or as part of a combination therapy regimen showed clinical activity in a subset of patients, underscores the need to improve our understanding of AURKA-regulated pathways that mediate tumor progression, including novel non-mitotic functions [ 17 , 21 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between Aurora A expression and tumour invasion and metastasis has been recently revealed. Kozyreva et al revealed that the combination of an Aurora A inhibitor with eribulin could lead to a synergistic increase in apoptosis in mammary tumours, as well as cytotoxic autophagy in metastases (24). Maimaiti et al reported that the simultaneous overexpression of Aurora A and CFL-1 associated with lymph node metastasis in thyroid cancer (25).…”
Section: Discussionmentioning
confidence: 99%